1997
DOI: 10.1121/1.419610
|View full text |Cite
|
Sign up to set email alerts
|

Forward-masked intensity discrimination: Duration effects and spectral effects

Abstract: Three experiments were completed to examine the effect of masker duration and spectrum on forward-masked intensity discrimination. Four listeners participated in each experiment. Intensity discrimination was measured in quiet and in the presence of forward maskers using adaptive forced-choice procedures. The standard duration was either short (10 ms) or long (250 ms) in experiment 1 and short (10 ms) in experiment 2. The standard always occurred 100 ms after the offset of the masker. In the first experiment em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…Compatible with this prediction, in both experiments by Oberfeld and Stahn (in press) the elevation of the intensity DL caused by the maskers was significantly smaller in conditions favoring the processing of maskers and targets as separate auditory objects or streams. Results from studies demonstrating that reducing the perceptual similarity between masker and target also reduces the masker-induced DLelevation (Schlauch et al, 1999(Schlauch et al, , 1997Oberfeld, 2008) would be directly compatible with the proposed framework of selective attention, while the three models introduced above cannot account for similarity effects without modifications (cf. Oberfeld, 2008).…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…Compatible with this prediction, in both experiments by Oberfeld and Stahn (in press) the elevation of the intensity DL caused by the maskers was significantly smaller in conditions favoring the processing of maskers and targets as separate auditory objects or streams. Results from studies demonstrating that reducing the perceptual similarity between masker and target also reduces the masker-induced DLelevation (Schlauch et al, 1999(Schlauch et al, , 1997Oberfeld, 2008) would be directly compatible with the proposed framework of selective attention, while the three models introduced above cannot account for similarity effects without modifications (cf. Oberfeld, 2008).…”
Section: Introductionsupporting
confidence: 56%
“…Previous experiments from our lab also found DL-elevations in the vicinity of 12 dB for a 60 dB SPL target presented together with an ipsilateral monaural masker (Oberfeld, 2008;Oberfeld and Stahn, in press). As discussed by Oberfeld (2008), smaller DL-elevations are observed if masker and target differ in spectrum or duration (Schlauch et al, 1997;Zeng et al, 1991).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Previous behavioral tests conducted on humans have shown that different durations of forward masker have different masking effects on the discrimination of probe intensity (Schlauch et al, 1997;Oxenham and Plack, 2000). So far, however, there is little literature available on its neuronal mechanism.…”
Section: Introductionmentioning
confidence: 99%